1988
DOI: 10.1530/jrf.0.0820563
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of intrascrotal temperature in normal and subfertile men

Abstract: Summary. Intrascrotal temperatures were measured bilaterally by a non-invasive method in 300 subfertile men (mean sperm count 21 \m=.\4\m=x\ 106/ml) and 30 normospermic control men (mean sperm count 118\m=.\7\ m=x\106/ml). The subfertile men had mean (s.d.) temperatures of 34\m=.\7\s=deg\C (0\m=.\8) for the right and 34\m=.\8\s=deg\C (0\m=.\7) for the left testis. The value for both testes of the control men was 33\m=.\4\s=deg\C (0\m=.\6). The difference ( 1\ m=. \ 3\ p=n-\ 1\ m=. \ 4\ s=deg\ C) was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
7

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 4 publications
(4 reference statements)
2
21
0
7
Order By: Relevance
“…We believe that the reduced ADC values observed in patients with varicocele may be related to these histopathological alterations. Unilateral varicocele has been known to cause an increase in both testicular temperature secondary to autoimmune and hormonal effects, according to the literature [19][20][21]. The reduced contralateral ADC values observed in our study may possibly be appearing as a result of these effects.…”
Section: Discussionsupporting
confidence: 51%
“…We believe that the reduced ADC values observed in patients with varicocele may be related to these histopathological alterations. Unilateral varicocele has been known to cause an increase in both testicular temperature secondary to autoimmune and hormonal effects, according to the literature [19][20][21]. The reduced contralateral ADC values observed in our study may possibly be appearing as a result of these effects.…”
Section: Discussionsupporting
confidence: 51%
“…Des neuf 6tudes dans lesquelles les temp6ratures scrotales ont 6t6 mesur6es des deux c6t6s [48,50,28,49,8,2,31,24,45], il appara~t une augmentation des temp6ra-tures scrotales moyennes droite et gauche par rapport h la population t6moin. Pour quatre de ces 6tudes [28,2,31,24], l'augmentation est par ailleurs significativement plus importante du c6t6 de la varicocble que du c6t6 oppos6 (Tableau 2).…”
Section: Temperatures Scrotales Et Varicoc~le Gaucheunclassified
“…L'intensit6 de cette augmentation n'est toutefois pas diff6rente de celle observ6e en cas de varicocble gauche [49,45]. …”
Section: Temperatures Scrotales Et Varicoc~le Bilat~raleunclassified
See 1 more Smart Citation
“…High ambient air temperatures may inhibit thermal loss through the scrotum, leading to a rise in testicular temperature [Procope, 19651. Infertile men without varicocele have been noted to have significantly higher intrascrotal temperatures than men without fertility problems, although the reasons for this temperature difference are not fully understood [Zorgniotti and Sealfon, 1988;Mieusset et al, 1987b1. Both animal and human studies have confirmed the sensitivity of sperm production to extrinsic heat [Henderson et al, 19861. Studies of male animals in elevated environmental temperatures have indicated that levels of reproductive hormones can be altered significantly, a factor that may be related to observed decreases in sperm production [Bedrak et al.…”
Section: Decreasedmentioning
confidence: 99%